Growth performance, carcass characteristics and meat quality of pearl and lavender varieties of guinea fowl (numida meleagris) in tropical climate of chhattisgarh - Neelmani Kerketta; Sharad Mishra (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present experiment was carried out to study the growth performance, carcass characteristics and meat quality of Pearl and Lavender varieties of guinea fowl (Numida meleagris) upto 14 th weeks of age in tropical climate of Chhattisgarh state in India.. The study revealed that at one day average body weight of Lavender variety was significantly (P< 0.05) higher than that of Pearl variety. However, no significant difference in mean body weight and body weight gain was observed in both varieties at the end of experimental period. The overall Feed Conversion Ratio during total experimental period of 14 week was observed to be significantly higher (P<0.05) in Lavender variety than. No significant difference was observed in dressing percentage and other carcass traits between both varieties. Similarly no significant difference was observed between different sensory characters of both the varieties.